A novel joint optimization of downlink transmission using physical layer security in cooperative 5G wireless networks - Zhi Chen; Peng Bai; Qiang Li; Su Hu; Dan Huang; Yi Li; Yuan Gao; Xiangyang Li (International Journal of Distributed Sensor Networks)
Privacy and perspective are attracting more and more attention from worldwide users, so security in wireless communication system has become popular in recent researches, especially the physical layer security in 5G systems. In this article, we discuss the physical layer security in 5G downlink transmission systems; we propose the joint optimization of subcarrier, power, and artificial noise to achieve the higher security rate, our proposed method could approach to the upper bound of the security rate rather than the other methods, respectively. Then, in the simulation part, we present the theoretical and system-level simulation, and the results indicate that our proposed method could effectively increase the security rate without losing the system transmission speed.